A Case of Childhood Non-Hodgkin's Lymphoma Presenting as Isolated Inguinal Lymphadenopathy - Abhipsa Samal; Anil Kumar Panda; Sasmita Mishra; Maitreyee Panda (Wolters Kluwer Medknow Publications, 2024)
Inguinal lymphadenopathy is a common condition encountered in routine clinical practice. It can be associated with various causes such as infections, inflammatory conditions, and neoplastic processes. We report the case of a young female presenting with an inguinal swelling with active discharge, which was initially suspected to have bacterial lymphadenitis, but subsequently diagnosed with non-Hodgkin's lymphoma. Such an atypical presentation of a hidden malignancy is very rare and has never been reported as per our knowledge.